The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1678-69712015/administracao.v16n3p76-108
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities, Innovation, and Overall Performance in Brazilian Export Firms

Abstract: This article extends the current research on innovation by investigating the relationship between innovative capabilities and export firms’ overall performance. From the perspectives of the resource-based view (RBV) and dynamic capability, we examine the differential and interactive effects of exploration and exploitation capabilities in product innovation for external markets and overall performance (direct and mediated by a new product). In addition, we test the moderating effect of market dynamism and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
(93 reference statements)
1
13
0
1
Order By: Relevance
“…Similar to previous studies (Cabral et al, 2015;Cao, Gedajlovic, & Zhang, 2009;Jansen, Van Den Bosch, & Volberda, 2006;Lisboa, Skarmeas, & Lages, 2013;O'reilly & Tushman, 2013;Wei et al, 2014), the result confirming the positive effect of DCs on the performance of companies listed in B3 S/A shows that, overall, investments in DC development enable BP improvement in Brazilian companies. Therefore, this outcome shows the importance of developing the skills and capabilities of these companies to (re)configure their assets/resources in order to adapt them to dynamic changes in the Brazilian market and to search for the appropriate improvement of their business performance (Eisenhardt & Martin, 2000;Teece, 2007Teece, , 2009Teece et al, 1997).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Similar to previous studies (Cabral et al, 2015;Cao, Gedajlovic, & Zhang, 2009;Jansen, Van Den Bosch, & Volberda, 2006;Lisboa, Skarmeas, & Lages, 2013;O'reilly & Tushman, 2013;Wei et al, 2014), the result confirming the positive effect of DCs on the performance of companies listed in B3 S/A shows that, overall, investments in DC development enable BP improvement in Brazilian companies. Therefore, this outcome shows the importance of developing the skills and capabilities of these companies to (re)configure their assets/resources in order to adapt them to dynamic changes in the Brazilian market and to search for the appropriate improvement of their business performance (Eisenhardt & Martin, 2000;Teece, 2007Teece, , 2009Teece et al, 1997).…”
Section: Resultssupporting
confidence: 87%
“…These authors found that the ambidextrous capability is related to company performance measured through a scale based on sales increase, on greater participation in the market, on gross ROE and on return in total assets. Based on exams in the direct and interactive effects of capabilities, either "exploitation" or "exploration", on product innovation for foreign markets and on general company performance, Cabral, Coelho, Coelho and Costa (2015) used data from 498 Brazilian exports companies in their research and concluded that exploitation capabilities influence product innovation and global performance (ambidexterity), whereas exploration capabilities, and their interaction with the exploitation ones (ambidexterity), influence the overall performance rather than product innovation.…”
Section: The DC -Bp Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Firms' resources and capabilities are the main determinants of firms' performance [30] and they are important in providing and sustaining their competitive advantage [31]. From a performance point of view J. D. E. O. Cabral et al reviewed several studies and summarized that firms typically develop and apply knowledge and skills that make them more innovative and increase their overall performance [32].…”
Section: Resources and Capabilitiesmentioning
confidence: 99%
“…External problems faced by MSMEs include the high transaction costs due to unfavorable business climate, scarcity of raw materials, technology, government policies as well as the acquisition of formal legality which is still a fundamental problem for MSMEs in Indonesia. Cabral et al, (2015) states that the factors that determine the capability of a business network are innovation. Innovation, which is one of the three dimensions of entrepreneurial orientation, is closely related to the ability to apply creativity in order to solve problems and opportunities to improve and enrich life.…”
Section: Introductionmentioning
confidence: 99%